Zoom Meeting Application as An Online Learning Media Innovation In Elementary School - Teguh Prasetyo (Universitas Veteran Bangun Nusantara, 2022)
Online Learning Innovation Based on Zoom Meeting Application is the policy selection taken at the Amaliah Elementary School of Bogor Regency. The Zoom Meeting application policy is used to support the implementation of effective learning in the pandemic period. The purpose of this study was to describe online learning based on Zoom Meeting at the Amaliah Elementary School as a school policy that chose the zoom meeting application as a learning media during a pandemic. The research method uses a qualitative approach with a case study design—the respondents used by teachers in the Elementary School of Amaliah. Data collection procedures use interviews, observation, and documentation for data analysis using triangulation. The study results imposed that teachers, students, and parents' support very quickly received the selection of zoom meeting applications. Zoom meeting-based online learning implementation can be used on online learning planning aspects, methods and strategies, and online learning assessment. Although the school provides supporting facilities, there are still obstacles to online learning-based zoom meetings. Furthermore, both teachers need to develop technological capabilities in presenting the learning in the pandemic and the science of their knowledge about various models of appropriate learning used in online learning.